Low Cost, Sensitive Impedance Detection of E. coli Bacteria in Food‐Matrix Samples Using Surface‐Imprinted Polymers as Whole‐Cell Receptors. Issue 23 (18th November 2021) - Stilman, Wouter; Campolim Lenzi, Mariana; Wackers, Gideon; Deschaume, Olivier; Yongabi, Derick; Mathijssen, Glenn; Bartic, Carmen; Gruber, Jonas; Wübbenhorst, Michael; Heyndrickx, Marc; Wagner, Patrick
Abstract : Herein, a biomimetic sensor platform that allows sensitive, onsite detection of Escherichia coli ( E. coli ) with a limit of detection of 30 cells mL −1 in both buffer suspension and rinsing water from an industrial food‐preparation machine is reported. Ultrathin surface‐imprinted polymers are combined with non‐Faradaic impedance spectroscopy to measure the increase in resistance at the solid‐to‐liquid interface due to the binding of target cells by the receptor layer. The detection limit reached with this sensing principle is determined using an established, commercial impedance spectrometer and a low‐cost, home‐built impedance unit. Cross‐selectivity tests, with both an unrelated bacterial species and four species belonging to the same Enterobacteriales order, show that the response is strongest for the target bacterium while only a small cross‐selectivity signal (≈10–25%) is visible for all other types of bacteria. Therefore, this sensor is not only fast and low cost, but also sensitive and selective. Sample preparation is minimal, which is an asset for onsite bacterial detection in a food industry context. Abstract : Herein, surface‐imprinted polyurethane coatings that bind E. coli bacteria selectively from complex food‐industry samples are reported. The receptors discriminate clearly between E. coli, which is an indicator in hygiene management, and closely related bacterial species. Combining these receptors with impedance spectroscopy as a quantitative readout method results in a detection limit as low as 30 cells mL −1 .